2022
DOI: 10.1039/d2qo01240e
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed switchable cyclization of alkyne-tethered α-bromocarbonyls: selective access to quinolin-2-ones and quinoline-2,4-diones

Abstract: Copper-catalyzed cyclization of alkynes has played a significant role in modern catalytic chemistry. However, the selective cyclization in this transformation is extremely limited by the uncontrolled reactivity of the vinyl-CuII...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Catalytic applications of heterogeneous metal catalytic systems such as nanoparticles (NPs), octahedral molecular sieves of manganese oxide (OMS-2), layered double hydroxides (LDH), polyoxometalates (POMs), and continuous flow reactors include hydrogenation, oxidation, reduction, coupling reactions, and multi component reactions (MCR). [1][2][3][4][5] In homogeneous catalysis, iron and copper catalysed sustainable organic transformations are widely developed for the modern synthesis of various functionalized molecules, [6][7][8][9] but heterogeneous metal systems have generally been more advanced due to a variety of factors, including size, shape, structure, charge, surface area, composite arrangements, fundamental material strength, synergistic effects of bimetallic systems, and more.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic applications of heterogeneous metal catalytic systems such as nanoparticles (NPs), octahedral molecular sieves of manganese oxide (OMS-2), layered double hydroxides (LDH), polyoxometalates (POMs), and continuous flow reactors include hydrogenation, oxidation, reduction, coupling reactions, and multi component reactions (MCR). [1][2][3][4][5] In homogeneous catalysis, iron and copper catalysed sustainable organic transformations are widely developed for the modern synthesis of various functionalized molecules, [6][7][8][9] but heterogeneous metal systems have generally been more advanced due to a variety of factors, including size, shape, structure, charge, surface area, composite arrangements, fundamental material strength, synergistic effects of bimetallic systems, and more.…”
Section: Introductionmentioning
confidence: 99%
“…8–10 In this scenario, the development of new catalysts that enables the introduction of oxygenated functions into C(sp 3 )–H bonds is a challenge undertaken by many research groups. 11–15…”
Section: Introductionmentioning
confidence: 99%
“…However, no 18 O incorporation product 2b was detected by ESI-HRMS analysis (Figure S1), which ruled out water as an oxygen source. There was an obvious decrease in the product yield when the reaction mixture was charged with nitrogen (Scheme c), which revealed that oxygen was significant for this transformation, and it might be a key oxygen source . Although the detailed reaction pathway remained to be clarified, a plausible mechanism for this reaction was proposed on the basis of the available experimental results and the literature (Scheme d). , First, selective activation of the alkyne by a Ag­(I) catalyst forms an (η 2 -alkyne)­silver complex I , which then endures an expeditious in situ aerobic oxidation to produce an active α-oxo silver carbenoid II intermediate.…”
mentioning
confidence: 99%